Unconventional phase transitions on hd and O2cryocrystals - Crespo, Y.; Laio, A.; Santoro, G.E.; Fabrizio, M.; Scandolo, S.; Tosatti, E. (Recent Contributions to Physics, 2015)
Both HD and O2 are molecular solids with an exceedingly well explored phase diagram under pressure. In this talk we focus in two unusual phase transition taking place at high pressures. First we study the unusual reentrant phase transition that the phase diagram of HD exhibits near 50 Gpa where a rotationally ordered (“broken symmetry”) crystalline phase (BSP) surprisingly transforms into a rotationally “disordered” high-symmetry phase upon cooling.